Charge-transfer between TCNQ and different sizes of InP quantum dots - Zhang, Xingao (Kansas State University, 2018)
Quantum dots (QDs) are novel semiconductors of interest for applications because of their special tunable properties. Among the many types of QDs, InP QDs attract attention because they do not have toxic-heavy-metal elements such as Cd or Pb. Charge-transfer (CT) is important in applications of InP QDs. CT consists of two or more molecules and some of them donate electrons and others accept those electrons. An understanding of CT between QDs with tetracyanoquinodimethane (TCNQ) is important for applications of QDs in photovoltaic and photocatalytic materials. TCNQ is an organic electron acceptor and CT complexes of TCNQ exhibit metallic electric conductivity. Previous research about CT between QDs and TCNQ examined PbS and CdSe QDs, but toxic-heavy-metals limit future application of these materials. So, it is important to research CT between InP QDs and TCNQ. This thesis examines how the amount of InP QDs (QD:TCNQ ratio) and diameters of InP QDs affect the CT between InP QDs and TCNQ. In this thesis, InP QDs are synthesized by a microwave-assisted ionic liquid (MAIL) method and InP QDs of different sizes are isolated using size-selective precipitation. Then, TCNQ-InP QD solutions are prepared with different ratios, with and without light, and with InP QDs of different sizes. These InP QDs and InP QDs-TCNQ samples are characterized using UV-Vis-NIR absorption, photoluminescence (PL), time-correlated single photon counting (TCSPC), and FT-IR spectroscopies. In Chapter 2, the details of synthesizing InP QDs, size selection, and preparation of different TNCQ-InP QD solutions are presented. Then, factors that affect the interaction between InP QDs and TCNQ and possible reasons for these factors are discussed. Based on calculations and experimental results, the carbon atom with the biggest amount of positive charge in TCNQ and phosphorous in InP QDs are likely the acceptor and donor, respectively. CT is affected by the amount of InP QDs in solution, and more InP QDs will reduce more TCNQ. The CT is also affected by the size of the InP QDs and enhanced by light.
Keywords: Quantum dots; Indium phosphide; Charge-transfer; Tetracyanoquinodimethane; Sizes